Act of Mar. 26, 1931, No. 225, § 4, Ark. Acts 705-06 - (:unkn) unknown (General Publisher, 1931)
Required the registration of machine guns to the Secretary of State.
--
Keywords: MACHINE GUN RESTRICTION